Fransisko de Goya, ili Kogato razumŭt spi - Lyudyulev (1980)
High contrast detail of Goya's Saturn Poster advertising play 'El sueño de la razón' ('The sleep of reason') by Antonio Buero Vallejo Original, performed at the Tears and Laughter Theatre, Sofia. Original title: Франсиско де Гоя, или Когато разумът спи PO-0347